Variable Topology Structure Design and Topology Analysis of a Variable-degree-of-freedom Single-loop Mechanism - Li Xia; Shen Huiping; Meng Qingmei; Li Ju; Yang Tingli (Jixie chuandong)
The degree of freedom of a special single-loop mechanism will change after passing through some special positions, which will lead to the change of its topology, kinematics/dynamics performance, and it is suitable for different application backgrounds. Firstly, a single-loop parallel mechanism composed of eight rotating pairs (R) is studied and designed, which has three motion modes: two degrees of freedom, four degrees of freedom and three degrees of freedom respectively, corresponding to three mechanisms. Then, the three main topological characteristics of the mechanism, such as position and orientation characteristic, degree of freedom and coupling degree, are analyzed and calculated in three motion modes, and the stability and transferability of the topological structures of the three mechanisms are analyzed. At the same time, the forward and inverse position solutions of the mechanism in motion modes 1 and 3 are analyzed. The work in this research provides a foundation for the research of reconfigurable parallel mechanisms based on this single-loop mechanism unit with variable degrees of freedom.